ANALISIS HUBUNGAN STATUS GIZI DENGAN GANGGUAN MENSTRUASI PADA REMAJA WANITA - Thaief, Kurniawan Arham (LPPMK STIKES Widyagama Husada, 2024)
Normal menstrual cycle is one component in describing the condition of reproductive health in women. Menstrual disorders that can be experienced by women vary widely, can occur in the form of menstrual cycle disorders (polymenorrhea, oligomenorrhea, amenorrhea), disturbances in the duration of menstruation that are too long (menorrhagia) or too fast (brachymenorrhea), and disturbances in the volume of blood that comes out during menstruation. (hypermenorrhea, hypomenorrhea). These disorders are influenced by many factors and one of them is nutritional status. The purpose of this study was to determine the relationship between nutritional status and the incidence of menstrual disorders in adolescent girls in Makassar City Senior High School. The research design used was observational analytic with a cross sectional research approach. This research was conducted at Public Senior High School 2 Makassar and there were 215 research samples that met the inclusion and exclusion criteria. The data of this study used primary data from the results of filling out questionnaires by respondents. The data was processed using SPSS with the Chi-Square test. The results of this study indicate that there is a significant relationship between nutritional status and menstrual disorders experienced by adolescent girls at Public Senior High School2 Makassar. Keywords: nutritional status, menstrual cycle, length of menstruation, menstrual blood volume.